1877 Dakota Terr. Rev. Codes 771 - (:unkn) unknown (My University, 1877)
Penal Code, ch. 23, § 294: Duel Defined. A duel is any combat, with deadly weapons, fought between two persons by previous agreement or upon a previous quarrel. § 295. Punishment for Fighting. Every person guilty of fighting any duel, although no death or wound ensues, is punishable by imprisonment in the territorial prison not exceeding ten years.
Keywords: DEFINITIONS; DUELING